Customers’ perception on service performance: A comparative analysis between foreign and local banks in Tanzania - G. S. , Fasha (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2020)
This study was a comparative study of the level of service performance between foreign and local banks. It focused on customers’ perception of service performance. This comparison was purposely done due to the fact that different international banks have opened their branches in Tanzania, and this has in one way or another forced to change the competitive landscape of the country’s banking industry. The study had a sample size of 380 respondents who were the customers of these banks. Confirmatory Factor Analysis at the second-order level was analyzed by looking at the Chi-square statistical values, Incremental Fit Index, the Tucker-Lewis Fit Index, the Comparative Fit Index, the Parsimony Normed Fit Index, and the Root Mean Square Error Approximation as the indicators of the model fit. Mean values were compared between foreign and local banks. The main findings from the study indicate that the fit indices indicated measurement invariance of service performance. quality of service, service innovativeness, and cash distribution facilities were perceived better by foreign banks’ customers than local banks’ customers.